Identification and characterization of a novel water-deficit-suppressed gene OsARD encoding an aci-reductone-dioxygenase-like protein in rice - Lin, T.; He, X.; Yang, L.; Shou, H.; Wu, P.
The aci-reductone dioxygenase (ARD)family common to bacteria, plants and animals is involved in the methionine salvage pathway. waterdeficit- suppressed gene, OsARD encoding an aci-reductone-dioxygenase-like protein, was identified from rice (Oryza sativa L.). Northern blot and reverse transcriptase-polymerase chain reaction (RT-PCR)analysis revealed that the OsARD expression is regulated by abiotic stresses and phytohormones. OsARD was mainly expressed in roots under flood conditions. It was suppressed by abiotic stresses including water deficit, high salinity and low temperature, and induced by ethylene and gibberellin acid (GA). Our results showed that the genes for S-adenosylmethionine (SAM)synthase and 1-aminocyclopropane-1-carboxylic acid (ACC)synthase were upregulated in RNA-interference (RNAi)transgenic rice plants with a significant reduction of OsARD expression. Furthermore, the expression of two genes for ethylene signal transduction, ETR2 and EIN3, increased in these RNAi transgenic plants, whereas the expression of ERF3 was suppressed. These results suggest that OsARD may play a role in the metabolism of methionine and ethylene in response to abiotic stresses.
Keywords: ABIOTIC STRESS; ACI-REDUCTONE DIOXYGENASE (ARD); METHIONINE SALVAGE PATHWAY; PHYTOHORMONE; ORYZA SATIVA L